A tilt in favour of the older generation, less fortunate - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2012)
Assistant Professor of Law Eugene Tan writes that although there are generally no significant handouts, offsets or goodies, Budget 2012 addresses some of the key genuine concerns of Singaporeans during the May 2011 General Election. It is also expected to generate a surplus of S$1.3 billion at a time when many advanced economies are in recession and with significant deficits.